How social opinion influences syntactic processing-An investigation using virtual reality. - Evelien Heyselaar; Peter Hagoort; Katrien Segaert (PLoS ONE, 2017)
The extent to which you adapt your grammatical choices to match that of your interlocutor's (structural priming) can be influenced by the social opinion you have of your interlocutor. However, the direction and reliability of this effect is unclear as different studies have reported seemingly contradictory results. We have operationalized social perception as the ratings of strangeness for different avatars in a virtual reality study. The use of avatars ensured maximal control over the interlocutor's behaviour and a clear dimension along which to manipulate social perceptions toward this interlocutor. Our results suggest an inverted U-shaped curve in structural priming magnitude for passives as a function of strangeness: the participants showed the largest priming effects for the intermediately strange, with a decrease when interacting with the least- or most-strange avatars. The relationship between social perception and priming magnitude may thus be non-linear. There seems to be a 'happy medium' in strangeness, evoking the largest priming effect. We did not find a significant interaction of priming magnitude with any social perception.